(untitled) (Revista Puertorriqueña de Psicologia, 2016)
The purpose of this study was to examine gender differences in adaptive vs. maladaptive social problem skills as assessed by the TEMAS (Tell-Me-A-Story) personality/narrative test. Samples included Hispanic girls and boys between the ages of 9-11, attending public schools in Puerto Rico or in New York. Results on the TEMAS were compared to another personality test, the Behavior Assessment System for Children - Self Report of Personality (BASC-SRP). Comparisons used one-way analysis of variance (ANOVA) in order to determine significant gender differences between the sites of PR and NY. For students sampled in Puerto Rico results showed significant gender differences in the TEMAS scale of Achievement Motivation, Reality Testing and Verbal Fluency. However, no significant gender differences were found in the New York sample. With the BASC gender differences were found in the clinical scale of Anxiety in the Puerto Rican sample, while no significant differences were found in the New York sample. Girls in PR showed a relative strength in several skills, whereas no such gender differences were noted in NY.